Effect of enriched bone-marrow aspirates on the dimensional stability of cortico-cancellous iliac bone grafts in alveolar ridge augmentation - Hendrik Naujokat; Klaas Loger; Aydin Gülses; Christian Flörke; Yahya Acil; Jörg Wiltfang (SpringerOpen, 2022)
Abstract Background The objective of the current study was to assess the clinical and radiological outcomes following autologous grafting from the iliac crest treated with autologous stem cells in-situ to reduce the postoperative bone graft resorption rate. Materials and methods The study group consisted of patients who underwent vertical augmentation of the jaws via bone grafts harvested from the iliac crest enriched with bone-marrow aspirate concentrates (stem cell group). The first control group (control) included 40 patients underwent a vertical augmentation with autologous bone grafts from the iliac crest. In the second control group, 40 patients received identical surgical procedure, whereas the autologous bone graft was covered with a thin layer of deproteinized bovine bone matrix and a collagen membrane (DBBM group). Clinical complications, implant survival, radiological assessment of the stability of the vertical height and histological evaluation at the recipient site have been followed up for 24 months postoperatively. Results No differences in terms of implant survival were observed in the groups. In the stem cell group, the resorption after 4-6 months was 1.2 ± 1.3 mm and significantly lower than the resorption of the control group with 1.9 ± 1.6 mm (P = 0.029) (DBBM group: 1.4 ± 1.2 mm). After 12 months, the resorption of the stem cell group was 2.1 ± 1.6 mm and significantly lower compared to the control group (4.2 ± 3.0 mm, P = 0.001) and DBBM group (resorption 2.7 ± 0.9 mm, P = 0.012). The resorption rate in the second year was lower compared to the first year and was measured as 2.7 ± 1.7 mm in the stem cell group (1-year bone loss in the time period of 12-24 months of 0.6 mm compared to 2.1 mm in the first 12 months). The resorption was significantly lower compared to the control group (4.7 ± 2.9 mm; P = 0.003, DBBM group: 3.1 ± 0.5 mm, P = 0.075). Conclusions Autologous bone-marrow aspirate concentrate could enhance the dimensional stability of the bone grafts and improve the clinical standard of complex reconstruction of the alveolar ridge. Even though the intraoperative cell enrichment requires an additional equipment and technical specification, it represents an alternative method for in-situ regeneration by osteogenic induction with a contribution of a manageable cost factor.